2013
DOI: 10.1038/srep01781
|View full text |Cite
|
Sign up to set email alerts
|

Photonic realization of nonlocal memory effects and non-Markovian quantum probes

Abstract: The study of open quantum systems is important for fundamental issues of quantum physics as well as for technological applications such as quantum information processing. Recent developments in this field have increased our basic understanding on how non-Markovian effects influence the dynamics of an open quantum system, paving the way to exploit memory effects for various quantum control tasks. Most often, the environment of an open system is thought to act as a sink for the system information. However, here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…To confirm this supposition and study how the memory effects of the environment affect the RDJA, we measured the non-Markovianity of the quantum system by employing the trace distance method, 29,31,44 which is given by…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm this supposition and study how the memory effects of the environment affect the RDJA, we measured the non-Markovianity of the quantum system by employing the trace distance method, 29,31,44 which is given by…”
Section: Resultsmentioning
confidence: 99%
“…31,44 In the future, the electron spin of the NV center could be used to address some fundamental physical questions, 28 such as the mathematical structure of the geometric space of non-Markovian quantum dynamical maps, the relevance of non-Markovianity in the study of the border between classical and quantum aspects of nature, and the use of non-Markovian quantum probes to detect nonlocal initial correlations in composite environments. Ultimately, with a deep understanding of and perfect control over the environment, the performance of QIP in solid-state system can be further improved.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for a bipartite open system where each subsystem locally interacts with a subsystem of a composite environment, the initial correlations between the subsystems of the environment can lead to * Corresponding author: nban@iop.vast.ac.vn non-Markovian behavior of the total open system, although the local dynamics of both subsystems of the system are Markovian [25]. Subsequently, an experimental demonstration of that phenomenon has also been achieved by using a photonic open system [26]. Although the unconventional mechanisms are few, there are still unknown strategies that would induce non-Markovian dynamics of an open quantum system.…”
Section: Introductionmentioning
confidence: 99%
“…The assumption of independent environments may be much restrictive in realistic experiments. The initial correlations between environments have been studied in the electromagnetic field [24][25][26]. Interestingly, it has been shown that initial environmental correlations can be used as a new resource for bringing memory effects in the dynamics of open quantum systems [24] and can induce correlations between the initially uncorrelated atoms [25].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been shown that initial environmental correlations can be used as a new resource for bringing memory effects in the dynamics of open quantum systems [24] and can induce correlations between the initially uncorrelated atoms [25]. Moreover, it has been verified experimentally that the information initially held in the environment can induce nonlocal memory effects in a photonic open system [26]. So we are very interested in what effects will be performed on the entanglement dynamics of the spin systems if there are initial environmental correlations.…”
Section: Introductionmentioning
confidence: 99%